![\huge \boxed{\mathbb{QUESTION} \downarrow}](https://img.qammunity.org/2022/formulas/history/college/1jyfph24cxomkgaamjtwx4vsi2y95urtq7.png)
- By substitution, justify that x = − 6 is a solution to x − 2 = − x − 14.
![\large \boxed{\mathbb{ANSWER\: WITH\: EXPLANATION} \downarrow}](https://img.qammunity.org/2022/formulas/engineering/college/8yws292u960at9h6j4zwjb6g91x4276wx6.png)
First, let's substitute the value of x as -6 in the equation.
![\tt \: x - 2 = - x - 14 \\ \dashrightarrow \: \tt \: ( - 6) - 2 = - ( - 6) - 14](https://img.qammunity.org/2022/formulas/biology/high-school/3mrn7dwguz4kr9twvtk15ncbrboshgwpx6.png)
Now, let's solve it.
![\tt \: ( - 6 ) - 2 = - ( - 6 ) - 14](https://img.qammunity.org/2022/formulas/biology/high-school/uz9d7ffh2cw5quv1ijfa5lcpr78yhv7een.png)
Subtract 2 from -6 to get -8.
![\tt \: -8=-\left(-6\right)-14](https://img.qammunity.org/2022/formulas/biology/high-school/f9rb965rdnd1ultcqzrx1nkd5kzhktx5jp.png)
The opposite of -6 is 6.
![\tt \: -8=6-14](https://img.qammunity.org/2022/formulas/biology/high-school/eqkb35vgmjiz8wnt20u9pdn51qcducjphg.png)
Subtract 14 from 6 to get -8.
![\tt \: -8=-8](https://img.qammunity.org/2022/formulas/biology/high-school/p0xny4f55a9359hqwl85xbeg9pfpsm2fyg.png)
Compare -8 and -8. We can see that both the LHS & RHS are equal to each other. So, hence we proved that x = − 6 is a solution of x − 2 = − x − 14.